WILL COVID-19 AFFECT THE QUALITY OF HUMAN DEVELOPMENT INDEX ? - Suparmono Suparmono (Universitas Pembangunan Nasional Veteran Yogyakarta, 2020)
This article aims to analyze the impact of Covid-19 on development, in particular, the quality of human development as measured by the human development index. The analysis is carried out using economic projections using the most appropriate projection approaches. From the analysis, it was found that the covid-19 that hit Kulon Progo Regency resulted in a decrease in the human development index. This decline brings the human development index to par with the conditions it was five years ago. Artikel ini bertujuan untuk menganalisis dampak Covid-19 terhadap pembangunan, khususnya kualitas pembangunan manusia yang diukur dengan indeks pembangunan manusia. Analisis dilakukan dengan menggunakan proyeksi ekonomi dengan menggunakan pendekatan proyeksi yang paling tepat. Dari hasil analisis diketahui bahwa COVID-19 yang melanda Kabupaten Kulon Progo mengakibatkan penurunan indeks pembangunan manusia. Penurunan ini membuat indeks pembangunan manusia sejajar dengan kondisi lima tahun lalu.